Fabrication and Characteristics of Silica Nanoparticle Monolayer Assembled by Spin Coating - Lan, Nguyen Thi Thanh; Hoang, Chu Manh (VNU Journal of Science: Mathematics - Physics; Vol 38 No 1DO - 10.25073/2588-1124/vnumap.4599, 2022)
In this paper, we report on a process for fabricating silica nanoparticle monolayer based on chemical synthesis and spin-coating. Spherical silica nanoparticles were synthesized by Stöber method using tetraethylorthosilicate as precursor. Close-packed silica nanoparticle monolayer was realized by optimizing the speed of spin-coating. Based on analyzing field emission scanning electron microscope (FE-SEM) images, the average diameter of silica spheres was determined and found of about 196 nm, with a standard deviation approximately ± 40 nm. The reflectance for the silicon substrate with spherical silica nanoparticle monolayers has been experimentally investigated at various spin-coating speeds. The experimental results are compared to those obtained from simulation data. The obtained results are useful for developing substrates having nanostructures for various applications in photonics and plasmonics. Keywords: Silica nanoparticles, Stöber method, spin coating, self-assembled monolayer